2018
DOI: 10.1002/ppul.24160
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to the diagnosis and treatment of hemoptysis in infants: A case series

Abstract: APCs should be considered as a differential diagnosis for pulmonary hemorrhage in infants after more common causes have been ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…In contrast, bronchial artery bleeding has not been reported as a common cause of hemoptysis in children. Instead, AP collaterals should be high in the differential diagnosis of hemoptysis in infants even without underlying CHD [9]. Zaidi et al reported seven infants with hemoptysis and no underlying CHD who underwent cardiac catheterization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, bronchial artery bleeding has not been reported as a common cause of hemoptysis in children. Instead, AP collaterals should be high in the differential diagnosis of hemoptysis in infants even without underlying CHD [9]. Zaidi et al reported seven infants with hemoptysis and no underlying CHD who underwent cardiac catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…Patients after the Fontan operation have a high likelihood of developing significant AP collaterals with an estimated hemoptysis rate of 4% [8]. Interestingly, AP collaterals have also been reported as the source of hemoptysis in children without CHD [9,10]. In our center, cardiac catheterization has been performed to identify the etiologies of hemoptysis in children and adults with and without underlying CHD.…”
Section: Introductionmentioning
confidence: 99%
“…In a contrasting case series, Zaidi et al reported a series of seven infants presenting with hemoptysis and severe respiratory distress at a mean age of 3 months. All had extensive evaluations at Advocate Children's Hospital with no specific cause identified.…”
Section: Rare Lung Diseasesmentioning
confidence: 99%
“…These findings are intriguing when considered alongside the Boston cohort; Welsh et al reported no cases of APCs, but also do not mention catheterization of any patients. The cases from Zaidi et al would have met diagnostic criteria for AIPHI based on clinical presentation, as current case definitions of AIPHI do not require cardiac catheterization to rule out APCs . Prior studies have failed to prove suspected associations between AIPHI and toxic mold exposure or von Willebrand disease, but a possible connection with APCs is an as‐yet unexplored hypothesis.…”
Section: Rare Lung Diseasesmentioning
confidence: 99%
See 1 more Smart Citation